Criminal Liability of Third Parties in the Crime of Embezzlement in Indonesia - Muhammad Nail Athallah; Kayus Kayowuan Lewoleba (Dinasti Research, 2024)
The function of law as a social controller is very important, especially in formulating effective policies and law enforcement, including in the context of criminal law that is oriented towards deterrent and restoration effects. This research aims to explore the criminal liability of third parties in the crime of embezzlement in Indonesia. The formulation of the problem includes the concept of third parties in embezzlement and their criminal liability. The method used is normative juridical legal research with statutory and conceptual approaches, and qualitative data analysis. The results show that third parties can be involved either directly or indirectly in the criminal act of embezzlement, and can be subject to criminal sanctions if proven to have knowledge of the origin of illegally obtained money. Legal handling of these third parties is important to close the loopholes for the main perpetrators and prevent money laundering. This research provides new insights into the complexity of criminal liability in embezzlement cases and its implications for law enforcement in Indonesia